THE MEDIATING ROLE OF RISK TOLERANCE IN THE RELATIONSHIP BETWEEN BEHAVIOURAL FACTORS AND INVESTMENT PERFORMANCE (International Journal of Management (IJM), 2024)
The current study aims at investigating the factors affecting investment Performance. Moreover, the mediating effect of risk tolerance was also tested. The study utilized a quantitative research design for that the data was collected using a structured questionnaire. The questionnaire was sent to 200 individuals out of those 189 complete questionnaires were received. The study framework had constructs namely heuristics, Prospect theory, were independent variables while investment performance making was dependent variable and risk tolerance was the mediating variable. All the latent construct were measured using multi-items based on 5-point Likert scales from 5 strongly disagree to 1 strongly disagree. This study set out to find the relationship behavioural factors and investment performance of individual investors with the mediating effects of risk tolerance. The Structural Equation Model has revealed that there is a significant and positive relationship between behavioural factors and investment performance of individual investors and this relationship is partially mediated by risk tolerance.